Kryptic or cryptic? The Divine Preconscious Model of the Incarnation as a concrete-nature Christology - Arcadi, James M. (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2016)
Andrew Ter Ern Loke has proffered a creative, novel, and bold model of the Incarnation as a contribution to analytic theological discussions of Christology. Recent work in this field has offered a distinction between abstract-nature and concrete-nature conceptions of natures. The former holds that entities have properties which entail their membership in a particular kind, the latter holds that being a member of a certain kind entails the having of certain properties. Loke’s model, what he calls the Divine Preconscious Model, holds that at the Incarnation the divine attributes of the Word were submerged into the Word’s preconscious, while the conscious of the Word took on certain human properties. This model, Loke holds, entails Christ’s full divinity and full humanity without falling into Apollinarianism or Nestorianism. However, I argue that because Loke avers that his model runs on a concrete-nature account of natures, he is not able to maintain the full humanity of Christ. I suggest two ways Loke might be able to maintain the integrity of his model, either by embracing a form of neo-Apollinarianism or by adopting the abstract-nature perspective of natures.